Reaching the Poor and Vulnerable in Myanmar : Lessons from a Social Protection and Poverty Reduction Perspective - Dutta, Puja Vasudeva (World Bank, Washington, DC, 2015)
Several government and development partner programs employ different approaches to ensure the inclusion of poor and vulnerable areas and people in Myanmar’s development. Buildingon this experience, this note aims to identify feasible options to effectively reach these groups, as government programs expand. Depending on program-specific choices about geographic focus andindividual, household eligibility, identifying poor and vulnerable areas and people in Myanmar can become more evidence-based, effective, and systematic, as better data become available and administrative systems develop. While targeting is currently done by individual programs, there can be important economies of scale in sharing and developing these systems in a coordinated manner so as to support multiple programs.